PERTANGGUNGJAWABAN PIDANA PENGADAAN PARKIR MENGGUNAKAN BADAN JALAN YANG MENGURANGI FUNGSI JALAN - Dananjaya, I Gede Yohanes; Sari, Diah Ratna (Kertha Negara : Journal Ilmu Hukum, 2023)
This paper aims to analyze how parking arrangements are in the codification of positive law in Indonesia and find out how criminal liability for parking procurement interferes with road functions. This paper uses a normative legal research method through a statutory and analytical approach. The results of this study indicate that parking activities using the road can reduce the function of the road, causing disruption of the function of the road. As a form of criminal responsibility, the perpetrator is threatened with imprisonment for a maximum of 18 months, or a maximum fine of Rp. 1,500,000,000.00 if it is done intentionally. Then if due to negligence, it is threatened with a maximum imprisonment of 3 months or a maximum fine of Rp. 300,000,000.00.